ANALISIS IMPLEMENTASI 5S (SEIRI, SEITON, SEISO, SEIKETSU, DAN SHITSUKE) PADA AREA BENGKEL - Radityo, Hening Pram; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2023)
5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) is Japan superior corporate culture conceptualized by Takashi Osada in 1980, about arrangement and neatness system in the environment like workshop, storing, and office. This culture is much implemented by Japan company in Indonesia, one of them is Auto 2000. The urgency of this research is to inspire other business entity’s work environment to apply 5S program as one means of lean operations. This study aims to describe the implementation of 5S on work environment of Auto 2000 Kediri Hasanuddin. This study uses 5S theory thus dissects in each variable S’ separately in account of appraising 7 areas. Data analysis method used is qualitative descriptive with triangulation for data collection method. Result describes that every area on workshop implements 5S significantly except machine restoration room. From 5 variables, shitsuke is not implemented. Areas with very good implementation are workshop area, SST room, and spare parts room. Implication of this study is becoming consideration for Auto 2000 Kediri Hasanudin in order to always keeps 5S performance that has already been good and improves the implementation performance that is not good, especially seiso that became main concern in TWC room, PDS room, and restoration room.